Graph Transformations for the Resource Description Framework - Braatz, Benjamin; Brandt, Christoph (Electronic Communications of the EASST, 2008)
The Resource Description Framework (RDF) is a standard developed by the World Wide Web Consortium (W3C) to facilitate the representation and exchange of structured (meta-)data in the "SemanticWeb". While there is a large body of work dealing with inference on RDF, a concept for transformation and manipulation is still missing. Since RDF uses graphs as a formal basis, this paper proposes the use of algebraic graph transformations with their wealth of well-known constructions and results for this purpose. It turns out that RDF graphs are an interesting application area for graph transformation methods, where some significant differences to classical graphs yield practically relevant solutions for features like attribution, typing and globally unique nodes.